Effects of UTAUT 2 Factors on Consumer Interest and Behavior in Digital Gold Investment: Evidence from the Tring! by Pegadaian Application - Vindya Nova Nur Khumairo; Minto Waluyo (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study investigates the effects of seven Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) constructs (Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, and Habit) on Behavioral Intention and Use Behavior among users of the Tring! by Pegadaian application for digital gold (e-gold) investment. The study employs a quantitative approach using Covariance-Based Structural Equation Modeling (CB-SEM) with AMOS 23 to analyze data from 180 respondents selected through purposive sampling. The results reveal that Performance Expectancy (?=0.284, p<0.001), Social Influence (?=0.163, p<0.05), Hedonic Motivation (?=0.202, p<0.05), and Habit (?=0.370, p<0.001) have positive and significant effects on Behavioral Intention, with Habit demonstrating the strongest influence. Conversely, Effort Expectancy, Facilitating Conditions, and Price Value do not show significant effects on Behavioral Intention. For Use Behavior, Behavioral Intention (?=0.388, p<0.001) and Facilitating Conditions (?=0.293, p<0.01) have positive and significant effects, while Habit does not have a significant direct effect (?=0.049, p>0.05). Mediation analysis confirms that Habit's influence on Use Behavior operates indirectly through Behavioral Intention. These findings contribute empirical evidence on technology adoption in the emerging digital gold investment sector and provide practical recommendations for improving digital investment services in Indonesia. The study also acknowledges limitations, including the absence of trust and perceived risk constructs, and suggests directions for future research. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and Infrastructure